ANALISIS DAN RANCANG BANGUN SISTEM KERJA LINK PADA MESIN GERGAJI RADIAL 4 ARAH - Richard Kurniawan; Michael Wijaya; Didi Widya Utama; Agus Halim (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: Four directions radial chainsaw is a chainsaw that have four cutting tools with link as it’s power continuer and using roller chain transmission. This machine is designed to improve the efficiency of cutting time. Especially in the furniture industry. Still, the stacking of wood cutting work can reduce the production capabilities. This essay will discussed about the link and transmission working system that is used in the machine. The method used in this design is VDI 2221. The order of this design is starting from the calculation of the force that required to cut the wood, the force that contains in the link, and the calculation of motor horsepower that is required. The wood used is falcate which is a four strong class